2024
DOI: 10.1111/1541-4337.13299
|View full text |Cite
|
Sign up to set email alerts
|

Application of DNA‐fueled molecular machines in food safety testing

Yujing Ma,
Ruipeng Chen,
Rui Zhang
et al.

Abstract: Food is consumed by humans, which is indispensable to human life. Therefore, considerable attention of the whole society has been paid to food safety. Over the last few years, dramatic social development has brought new challenges to food safety, making developing new and quick methods for on‐site food safety testing an important necessity. As a result, DNA‐fueled molecular machines, characterized by high efficiency, accuracy, and sensitivity in testing, have come into the spotlight, based on which sensors can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…43 However, as the study progressed it was found bipedal and multipedal DNA walkers exhibit higher stability and higher velocity. 37 For example, Wang et al designed an electrochemical biosensor based on a bipedal DNA walker, which…”
Section: Walking Strandmentioning
confidence: 99%
See 1 more Smart Citation
“…43 However, as the study progressed it was found bipedal and multipedal DNA walkers exhibit higher stability and higher velocity. 37 For example, Wang et al designed an electrochemical biosensor based on a bipedal DNA walker, which…”
Section: Walking Strandmentioning
confidence: 99%
“…However, as the study progressed it was found bipedal and multipedal DNA walkers exhibit higher stability and higher velocity. 37 For example, Wang et al designed an electrochemical biosensor based on a bipedal DNA walker, which ultimately contributes nearly 5-fold synergistic enhancement of the current signal compared to a unipedal walker, and successfully realizing the highly sensitive detection of target. 44 In addition, Mao et al developed a multipedal DNA walker for the first time to achieve ultra-sensitive analysis of circulating tumor cell (CTCs).…”
Section: Dna Walkersmentioning
confidence: 99%